2022
DOI: 10.21608/adjg.2022.103255.1430
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pomegranate and Banana Extracts on Microshear Bond Strength of Resin Composite to Bleached Bovine Enamel: An In-Vitro Study

Abstract: Purpose: To evaluate the effect of pomegranate and banana extracts (natural antioxidants) versus ascorbic acid (synthetic antioxidant) prepared in 10% and 15% concentrations on microshear bond strength (µSBS) to bleached enamel. Materials and Methods: A total of 56 bovine incisors were selected for the current study. Forty teeth were used for microshear bond strength and divided into 5 groups according to antioxidant type; Group 1: No bleaching + No antioxidant (negative control), Group 2: Bleaching + No antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
2
0
3
Order By: Relevance
“…Studies on dental substrates bleached with high-concentrated hydrogen peroxide reported that the P. granatum solution could fully or partially restore the bond strength of the restorative material to enamel and dentin [ 13 27 28 ]. Unbleached dentin treated with 20% pomegranate solution increased the bond strength compared to the untreated control [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on dental substrates bleached with high-concentrated hydrogen peroxide reported that the P. granatum solution could fully or partially restore the bond strength of the restorative material to enamel and dentin [ 13 27 28 ]. Unbleached dentin treated with 20% pomegranate solution increased the bond strength compared to the untreated control [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies clarify the benefits of P. granatum in Dentistry, only a few used P. granatum extract to treat tooth surfaces before resin composite application, mainly in bleached surfaces [ 13 18 20 27 28 30 31 32 ]. Besides, to the best of our knowledge, there is only 1 that investigated the P. granatum on eroded dentin and 2 that assessed the bond strength of resin composite to dentin pretreated with P. granatum extract [ 17 29 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diferenças nos perfis de compostos fenólicos foram observadas entre as partes da romã (casca, semente e fruto), sendo as amostras da casca, as que apresentaram maior concentração de compostos fenólicos antioxidantes (Akhtar et al, 2015;Russo et al, 2018). Apesar de inúmeros estudos elucidarem os benefícios do extrato de romã (Bhandari 2012;Akhtar et al, 2015;Peršurić et al, 2020), poucos utilizam esse extrato para tratamento da superfície dental previamente a inserção do material resinoso, sendo a maioria deles realizada em dente o recebeu agente clareador (Sharafeddin & Farshad, 2015;Souza-Gabriel et al, 2020;Suratno et al, 2021;Abodahb et al, 2022).…”
Section: Int Roduçãounclassified
“…Em 2015, Sharafeddin & Farshad não encontraram diferença na resistência de união da resina composta ao esmalte clareado com peróxido de carbamida 15% e tratado com chá de romã 10%. No entanto, estudos recentes em substratos clareados com peróxido de hidrogênio acima de 35%, verificaram que a solução de P. granatum foi capaz de reestabelecer, total ou parcialmente, a resistência adesiva do material restaurador ao esmalte (Suratno et al, 2021;Abodahb et al, 2022) e à dentina (Souza-Gabriel et al, 2020). Esses resultados evidenciam que os compostos fenólicos antioxidantes da solução de romã possam ter capturado os radicais O2 livres da superfície e favorecido a adesão do sistema resinoso (Souza-Gabriel et al, 2020;Suratno et al, 2021).…”
Section: Int Roduçãounclassified
See 1 more Smart Citation